Vietnam : Technical Assistance Report-National Accounts Statistics Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
At the request of the General Statistics Office (GSO) of Vietnam, a technical assistance mission helped with the preparation of the next rebase of national accounts. The current base year 2010 needs to be updated to incorporate recent structural changes. A work plan was established to compile a new national accounts benchmark for 2020 and publish rebased estimates in March 2023. The mission focused on a better incorporation of non-observed activities as well as the development of supply and use tables and input-output tables for the new benchmark. This mission was funded by the IMF's Data for Decisions project with the overall goal of putting more and better data in the hands of decision-makers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Vietnam